Survey and characterization of genomic features for leveraging the bacterium Pseudomonas putida KT2440 as a bioconversion platform - Siqueira, Guilherme Marcelino Viana de (2025)
The Gram-negative bacterium Pseudomonas putida KT2440 has gained traction as a microbial host in fermentative processes due to its unique set of biochemical and physiological traits, including a highly flexible central carbon metabolism, innate tolerance to aromatic compounds, solvents, and metals, as well as to its relative safety and amenability to genetic manipulation. Yet, a significant portion of its genetic potential remains poorly understood, and that is compounded by discrepancies found across open genomic annotation knowledge bases and by the relative scarcity of genetic tools specifically designed for the optimization of heterologous expression in this host, two factors that hinder its applicability in broader settings. In this context, the present study aims to address different aspects of P. putida as a bioproduction host by i) investigating the physiological response of this organism to acetate, a microbial growth inhibitor present in lignocellulosic hydrolysates; ii) integrating genomic annotations and experimental data from open repositories included in the National Center for Biotechnology Information (NCBI) and other open databases; and iii) developing and characterizing a new modular vector that utilizes transcriptional terminators identified in a metagenomic soil library. The collection of results presented here reveals new targets for engineering new strains of P. putida KT2440 for biofuel production in acetate-rich media, sheds light on inconsistencies across genomic annotations widely used in the literature, and reinforces that utilizing biological parts recovered from environmental sources can be a strategy to benefit heterologous expression in P. putida in comparison to established laboratory hosts, such as Escherichia coli. As a result, this work aims to provide a new perspective on the biotechnological potential of this microbial host, highlighting its role as an useful tool in addressing the challenges posed by the bioeconomy.